1,4-Bis(1H-benzimidazol-2-yl)benzene methanol monosolvate - Hua Huang (Acta Crystallographica Section E, 2011)
The asymmetric unit of the title compound, C20H14N4·CH4O, contains two independent half-molecules, each located on an inversion centre, and a methanol solvent molecule. The benzimidazolyl groups form different dihedral angles [24.0 (1) and 11.6 (1)°] with the plane of the central benzene ring in the two molecules. In the crystal, a two-dimensional network is formed through N—H... N, N—H...O and O—H...N hydrogen-bonding interactions between the benzimidazole units and methanol solvent molecules. π–π stacking interactions also occur between the benzimidazole rings of adjacent molecules, with centroid–centroid distances of 3.720 (14) Å and interplanar distances of 3.53 (1) Å .